Itsmid sebagai Eyeliner dalam Kosmetika Dunia Muslim: Studi Takhrij dan Syarah Hadis - Syfa Nurhofipah (Jurnal Riset Agama, 2021)
This study aims to discuss the hadith related to eyeliner. This study uses a qualitative approach through the method of takhrij and syarah hadith analysis of contemporary issues. The results of this study found that the hadith about itsmid is closely related to eyeliner in the contemporary era. The quality status of itsmid hadith is considered authentic so that it can be used as a basis for Islamic practice. The discussion of this study explains that eyeliner has been found since the time of the Prophet known as eye shadow (al-itsmid) as a health to grow eyelashes in addition to sharpening the eyes. While eyeliner in the contemporary era is more used for the beauty of women and the use of eye shadow is more as make up. The conclusion of this study is that the use of eyeliner in the contemporary era is more susceptible to health than eye shadow made from al-itsmid. This study recommends millennials, especially women, to use make-up that is sterile and safe for health.